2019
DOI: 10.1101/813378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly expressed miR-375 is not an intracellular oncogene in Merkel cell polyomavirus-associated Merkel cell carcinoma

Abstract: 201-1836945 2 AbstractPurpose. miR-375 is a highly abundant miRNAs in Merkel cell carcinoma. miR-375 may act as a tumor suppressor or oncogene depending on the cell context. While miR-375 is present as circulating free in the serum of patients with advanced MCC and thus serves as surrogate marker for tumor burden, its function within MCC has not been established.Methods. miR-375 knockdown was performed using miR-375 antagomiRs via lipofectamine transfection or nucleofection in classical MCC cell lines WaGa and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In most cancers, miR-375 has been deemed a tumor suppressor [ 36 ], but it also functions as an oncogenic miRNA depending on the cellular context [ 32 , 33 ]. We recently reported that knockdown of miR-375 in MCC cell lines has—at best—minimal effects on cell survival, proliferation and morphology [ 37 ]. Highly efficient knockdown did not alter any of the signaling pathways involving miR-375 target genes [ 37 ], thus posing the question about the functional role of this highly abundant miRNA in MCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cancers, miR-375 has been deemed a tumor suppressor [ 36 ], but it also functions as an oncogenic miRNA depending on the cellular context [ 32 , 33 ]. We recently reported that knockdown of miR-375 in MCC cell lines has—at best—minimal effects on cell survival, proliferation and morphology [ 37 ]. Highly efficient knockdown did not alter any of the signaling pathways involving miR-375 target genes [ 37 ], thus posing the question about the functional role of this highly abundant miRNA in MCC.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that knockdown of miR-375 in MCC cell lines has—at best—minimal effects on cell survival, proliferation and morphology [ 37 ]. Highly efficient knockdown did not alter any of the signaling pathways involving miR-375 target genes [ 37 ], thus posing the question about the functional role of this highly abundant miRNA in MCC. Based on our observation that miR-375 is present in MCC conditioned cell culture medium as well as sera of MCC patients [ 27 ], it may function as an exosome-shuttle miRNA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, two studies argue that miR-375 suppresses growth in PC-3 cells and two studies claim the opposite. Furthermore, the sobering lack of a phenotype from loss of miR-375 expression in MCC cell lines suggests that miR-375 may have functions outside the tumor cells, as suggested by Fan et al [ 99 ] and supported by studies in prostate cancer [ 114 ]. An exosomal function of miR-375 must be explored in more detail, as well as the idea that exosomes loaded with sufficient amounts of miR-375 can be transferred to adjacent cells to mediate an effect in the recipient cells.…”
Section: Mir-375: An Indeterminant Oncogene a Mirage Of A Tumor Smentioning
confidence: 91%
“…For example, massive un-physiological overexpression of miR-375 may “always” result in a growth-suppressive phenotype in vitro in prostate cancer cells or for that matter any cancer cell (e.g., oral cancer). To explore this issue in a more unbiased fashion and shed light on the unsatisfactory conclusions about miR-375’s role in cancer, we selected ten of the most recent publications [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ] and ten of the most cited publications [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ] that deal with miR-375 and determined the pro- or anti-growth outcomes of its overexpression or inhibition in these studies. Overexpression using a miR-375 mimic produced growth inhibition and/or induction of apoptosis in 16 of the 17 studies, while miR-375 inhibition had either no effect or mild pro-growth effects in 7 of 10 studies.…”
Section: Mir-375: An Indeterminant Oncogene a Mirage Of A Tumor Smentioning
confidence: 99%
See 1 more Smart Citation